Kinerja Usaha UMKM Makanan Ringan Berbasis Motivasi, Kemampuan, Kinerja Usaha dan Komitmen Organisasi - Sudarijati, Sudarijati; Kartini, Tini; Alam, Saepul (Jurnal Ilmiah Global Education, 2025)
This study aims to analyze the effect of motivation and ability on business performance by considering the role of organizational commitment as an intervening variable in snack food MSMEs located in Central Bogor District. The samples used in this study were all snack food MSMEs that were actively registered and assisted by the Bogor City Cooperative and SME Office, with a total of 108 MSME units. The approach used in this research is descriptive and verification, with data analysis using the path analysis method. The results showed that motivation and ability have a direct and positive influence on organizational commitment and on business performance. In addition, organizational commitment acts as an intermediary variable in the relationship between motivation and ability to business performance. Based on these findings, it is recommended that business actors can further improve motivation, ability, and organizational commitment to encourage more effective business performance improvement.